Hydrogeochemistry Characteristics Of Water And Stream Sediment Originated From Activities Surrounding Gunung Paku, Pengkalan Hulu, Perak - Wan Saberi, Wan Ahmad Nazmi (Universiti Sains Malaysia, 2018)
Gunung Paku near Klian Intan, Perak, located within the western Tin Belt of Peninsular Malaysia, is a primary tin deposit in Malaysia mined since 200 years ago, contributing 3–5% of tin ore concentrates previously, and recently over 70% of the Malaysian tin. Gunung Paku is associated with biotite granite (184–230 Ma) of the Main Range Granitoid which extends up to the southern part of Peninsular and Central Thailand. The primary tin mineralization style at the Gunung Paku is mainly associated with widespread occurrence of sheet‐like quartz veining systems parallel to the strike of the host rocks and confined within a narrow N–S trending fault zone. The mineralization formed within a thick sequence of metasedimentry rock that belongs to the Baling Formation of Palaeozoic age. From the geological survey, Sungai Belimbing, Sungai Air Jernih, Sungai Kepayang, Sungai Rui, Sungai Kuak, Sungai Hitam and Sungai Duri are chosen for hydrogeochemistry characteristics of sediment and water. The purpose is to know the effect of activities surrounding to the stream sediment and water quality. Representative samples are subjected to several test such as X-ray fluorescence, X-ray diffraction and Inductively Coupled Plasma. From the XRF analysis, the stream soil sediment from the stream surrounding Gunung Paku shown that the composition of metal is low except element of Al and Fe. The analysis of ICP show that the concentrations of metals for B1, B2 and B3 are high cause of activities surrounding compared with other water samples and also the lowest of pH values and the highest of electrical conductivity.